Madzhab-madzhab antropologi - Syam, Nur, 1958- (Yogyakarta : LKiS, 2007)
Anthropological research on local culture in Jawa Timur Province.
Includes bibliographical references : (p. 215-222) and index.
Keywords: Anthropology -- Research